Muatan Lokal in Mathematics Learning Process at Schools in Aceh Province - Putra, Mulia; Baba, Takuya (Universitas Ahmad Dahlan, 2018)
This research aims to describe muatan lokal, a subject discussing local culture content in Indonesia, and to analyze mathematics learning process at schools in Aceh Province based on Bishop's universal mathematical activities. The collection and analysis of the data used a qualitative approach. Besides the qualitative approach, we also used an ethnomathematical approach to make a rigorous description of muatan lokal and its existence in the mathematics learning process at the schools. This research found that the current implementation of muatan lokal in Aceh was still in progress of development. In fact, however, many schools have already implemented the subject muatan lokal based on the Indonesian Ministry of Education and Culture’s regulation. Furthermore, we could identify the existence of mathematics in the teaching material of muatan lokal subject. However, the connection between both muatan lokal and mathematics as subjects at school is too weak for the VII grade of junior high schools in Aceh.